Risk of Migraine in Patients With Asthma: A Nationwide Cohort Study. Issue 9 (March 2016) - Peng, Yi-Hao; Chen, Kuan-Fei; Kao, Chia-Hung; Chen, Hsuan-Ju; Hsia, Te-Chun; Chen, Chia-Hung; Liao, Wei-Chih
Abstract : Abstract: Asthma has been described as an "acephalic migraine" and "pulmonary migraine." However, no study has investigated the temporal frequency of migraine development in patients with asthma, and the results of previous studies may be difficult to generalize. We investigated the effect of asthma on the subsequent development of migraine by using a population-based data set in Taiwan. We retrieved our study sample from the National Health Insurance Research Database. Specifically, 25, 560 patients aged 12 years and older with newly diagnosed asthma were identified as the asthma group, and 102, 238 sex and age-matched patients without asthma were identified as the nonasthma group. Cox proportional-hazards regression models were employed to measure the risk of migraine for the asthmatic group compared with that for the nonasthmatic group. The risk of migraine in the asthmatic group was 1.45-fold higher (95% confidence interval 1.33–1.59) than that in the nonasthmatic group after adjustment for sex, age, the Charlson comorbidity index, common medications prescribed for patients with asthma, and annual outpatient department visits. An additional stratified analysis revealed that the risk of migraine remained significantly higher in both sexes and all age groups older than 20 years. Asthma could be an independent predisposing risk factor for migraine development in adults.